Stakeholder Engagement: Development of Sustainable Tourism Based on Local Wisdom - Sucihatiningsih Dian Wisika Prajanti; Said Nur Octavianto; Widiyanto Widiyanto (Universitas Negeri Semarang, 2025)
The development of sustainable tourism in Pati Regency, grounded in local wisdom, has been hindered by several factors, including structural ego issues, overlapping policies, and inadequate stakeholder collaboration. This study analyzes efforts to support tourism development, examines the impact of various variables (factors), and assesses the influence of stakeholders (actors) in sustainable tourism initiatives based on local wisdom in Pati Regency. The methodology integrates qualitative and quantitative approaches, employing the MICMAC and MACTOR methods. MICMAC analysis identifies core variables such as uniqueness and historical value, regional income, stakeholder relationships, community involvement, and utilizing local wisdom in tourism development. MACTOR analysis reveals key stakeholders namely, the Tourism and Culture Office (Dinporapar), the Cooperative and Small and Medium Enterprises Office (Dinkop), and the local community as central actors in sustainable tourism development. The findings from the MICMAC and MACTOR analyses provide a basis for formulating a comprehensive strategy to accelerate sustainable tourism development rooted in local wisdom in the Pati Regency. Further research may incorporate additional external variables and stakeholders to support advancing tourism models based on local creative economy initiatives.